2004
DOI: 10.1016/j.lab.2004.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Lack of good correlation of serum CC-chemokine levels with human immunodeficiency virus-1 disease stage and response to treatment

Abstract: Three CC-chemokines-MIP-1alpha (CCL3), MIP-1beta (CCL4), and RANTES (CCL5)-are natural ligands for the human immunodeficiency virus-1 (HIV-1) coreceptor CCR5. To determine correlations between CC-chemokines and HIV-1 disease stage or response to treatment, we examined serum levels of MIP-1alpha, MIP-1beta, and RANTES in 60 infected patients during 18 months while they were taking highly active antiretroviral therapy (HAART). Our results demonstrate that serum levels of MIP-1alpha and RANTES were increased in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…Ye Ping et al demonstrated that there were no significant differences among the four clinical stages of HIV-1 infection in the serum levels of CC-chemokines [47] and we also observed no significant differences among the two groups of patients with CD4 + T cell between 200-400 cells/μL and CD4 + T cell> 400 cells/μL for MIP-3α. The weakness of our study is that the levels of MIP-3α have not been explored and measured in the fluid at the recto-colonel level.…”
Section: Discussionsupporting
confidence: 62%
“…Ye Ping et al demonstrated that there were no significant differences among the four clinical stages of HIV-1 infection in the serum levels of CC-chemokines [47] and we also observed no significant differences among the two groups of patients with CD4 + T cell between 200-400 cells/μL and CD4 + T cell> 400 cells/μL for MIP-3α. The weakness of our study is that the levels of MIP-3α have not been explored and measured in the fluid at the recto-colonel level.…”
Section: Discussionsupporting
confidence: 62%
“…[33][34][35] This raises the possibility that the higher serum levels of MIP-1a in obese individuals could affect HIV-1 entry or replication in peripheral CD4 + T cells, but current published data on the relationship between serum MIP-1a and HIV replication or the response to ART are conflicting. [36][37][38] We hypothesize that the increased circulating MIP-1a derives from adipose deposits, but further studies are needed to determine whether higher serum levels affect the HIV disease state or are simply a reflection of excess adiposity.…”
Section: Koethe Et Almentioning
confidence: 99%
“…However, there is a cautionary note: the biomarker potential of CCR5 ligands requires consideration of the fact that although antiviral immunity is afforded by release of HIV-suppressive CCR5 ligands from activated leukocytes, serum levels of these biomarkers may correlate poorly with HIV-AIDS outcomes [114] and high levels of chemokines by imparting pro-inflammatory effects [115] may accelerate disease progression.…”
Section: Mendelian Randomization and Hiv-associated Outcomes: Case Stmentioning
confidence: 99%